Conventional Implicature in Patient Package Inserts - Ruben Dharmawan (PRASASTI: Journal of Linguistics, 2013)
The study aims to investigate the legal aspects and the informative aspects, especially the conventional implicature of patient package inserts. Eighty five patient package inserts were collected from licensed drugstores in Surakarta and the surroundings from February 1, 2013 to February 15, 2013 to be qualitative content analyzed. It was found that out of eighty five inserts, seventy four (87 percents) gave explanation in Indonesian only; eight package inserts (9.4 percents) had English and Indonesian translations; and three (3.6 percents) had English texts only. It seems that most of the pharmaceutical companies do not think original leaflets important for drug users or public readers. The companies focus more on legal aspects than on good benefit that might be gained by attaching the original ones. Without original brochures, it is not known whether the translation meet the Readability Guideline expectations: faithful translation, understandable and patient-friendly. Eight package brochures having English and Indonesian translation were discussed. Three of them contained sentences with inference markers of conventional implicature. The inference markers were: even, therefore and but; their conventional implicature were explained by way of the drugs mechanisms and metabolisms in human body. The scarcity of conventional implicature indicated by only three words (even, therefore and but) or three sentences among about eight times five hundred words or around four hundred sentences could be an indication of appreciable efforts of the English writers to meet understandable and patient-friendly information. They seemed to avoid conventional implicature that might be understood differently by many drug users or public readers. Key words: legal and informative aspects, readability, patient-friendly.